A Systematic Review of Muscle Synergies during a Walking Gait to Define Optimal Donor-Recipient Pairings for Lower Extremity Functional Reconstruction. Issue 8 (15th August 2022) - Magrath, Walker J.; Qiu, Cecil S.; Hanwright, Philip J.; Tuffaha, Sami H.; Khavanin, Nima
Abstract : Background: Functional lower extremity reconstruction primarily aims to restore independent ambulation. We sought to define the synergies recruited during a walking gait to inform donor selection for various motor deficits. With these findings, we discuss the functional neuromuscular components of independent gait with the goal of informing lower extremity reconstruction. Methods: A systematic review was performed using MEDLINE for articles published between January 2000 and December 2020. Search terms included (1) "motor module(s), " "synergy, " "motor pattern, " or "motor primitive" and (2) "gait, " "walking, " "ambulation, " or "locomotion." Abstracts/full texts were reviewed by two independent reviewers. Results: A total of 38 studies were selected. The average reported number of synergies and variance accounted for was 4.5 ± 0.9 and 88.6% ± 7.7%, respectively. Four motor modules were conserved across nearly all studies. Conclusions: Walking can be reduced to the sequential activation of four motor modules. Activities during the stance phase are critical for both standing stability and forward progression and should be prioritized for reconstruction with the goal of preserving efficient gait. Muscles recruited during swing, except those used for ankle dorsiflexion, are less prone to injury and benefit from greater redundancy, less often necessitating reconstruction. With the emphasis on stability during stance, several synergistic or sometimes even antagonistic tendons can be used to replace their counterparts and restore efficient, independent ambulation. With a finite supply of donor tissues, and in the absence of well-defined clinical outcomes data, this research allows us to effectively prioritize reconstructive goals and maximize patient outcomes.